2017
DOI: 10.1097/shk.0000000000000810
|View full text |Cite
|
Sign up to set email alerts
|

Preadministration of Hydrogen-Rich Water Protects Against Lipopolysaccharide-Induced Sepsis and Attenuates Liver Injury

Abstract: Despite significant advances in antibiotic therapy and intensive care, sepsis remains the most common cause of death in intensive care units. We previously reported that molecular hydrogen (H2) acts as a therapeutic and preventive antioxidant. Here, we show that preadministration of H2-dissolved water (HW) suppresses lipopolysaccharide (LPS)-induced endotoxin shock in mice. Drinking HW for 3 days before LPS injection prolonged survival in a mouse model of sepsis. The H2 concentration immediately increased in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
33
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(36 citation statements)
references
References 33 publications
3
33
0
Order By: Relevance
“…Unfortunately, the limited sensitivity of the ELISA kit prevented us from analyzing endotoxins in the present study. However, previous studies reported that H 2 alleviated endotoxin-induced liver injury in rodents by reducing inflammation and cell apoptosis[20,22,23]. Taken together, the evidence indicates that HRW administration helps maintain permeability, mucosal structure and barrier function in intestine and improves the gastrointestinal microenvironment for bacteria that protect against EtOH-induced liver injury.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…Unfortunately, the limited sensitivity of the ELISA kit prevented us from analyzing endotoxins in the present study. However, previous studies reported that H 2 alleviated endotoxin-induced liver injury in rodents by reducing inflammation and cell apoptosis[20,22,23]. Taken together, the evidence indicates that HRW administration helps maintain permeability, mucosal structure and barrier function in intestine and improves the gastrointestinal microenvironment for bacteria that protect against EtOH-induced liver injury.…”
Section: Discussionmentioning
confidence: 72%
“…Similar antioxidant phenomena were observed in many oxidative stress-related diseases, especially CCl 4 - , endotoxin-, acetaminophen- and ischemia / reperfusion -induced hepatic injuries in rodents[21-27,32,40]. A number of studies reported that H 2 reduces oxidative stress not only directly but also indirectly, by regulating anti-oxidative signal transduction, including nuclear factor erythroid 2-related factor 2 (Nrf-2) and sirtuin 1 (Sirt1)[14,18,20,35]. Antioxidants regulated by Nrf-2 via an antioxidant response element-driven mechanism include SOD, GSH-Px, CAT, heme oxygenase-1 (HO-1), peroxiredoxins, etc [48].…”
Section: Discussionmentioning
confidence: 99%
“…Activation of these CDK inhibitors generates ROS, which act as signaling molecules to promote the continuous induction of cellular senescence 30 . Remarkably, drinking HW ameliorates oxidative stress in animal disease models, including the Apoe −/− mouse model of atherosclerosis 16 , and in human clinical trials, including metabolic syndrome 17 , 31 and rheumatoid arthritis 32 . One possible mechanistic explanation for the suppressive effect of HW on cellular senescence is that the lowering of ROS by HW downregulates DDR pathways.…”
Section: Discussionmentioning
confidence: 99%
“…For example, drinking HW ameliorated symptoms of Parkinson’s disease in a rat model, whereas both H 2 gas inhalation and lactulose-induced production of intestinal H 2 did not 15 . We recently reported that pre-administration of HW was sufficient to attenuate septic inflammation in mice, strongly indicating that the therapeutic effects of HW derive from a mechanism distinct from the direct reduction of ROS by H 2 16 .…”
Section: Introductionmentioning
confidence: 99%
“…Notably, H 2 has no risk of flammability or explosion at a concentration of less than 4.7% in air, as commented by the authors. Since then, hydrogen-rich water has been widely used as alternatively therapeutic topics on many medical diseases [ 14 , 15 , 16 , 17 , 18 ]. Moreover, acidic cosmetic water acts against Staphylococcus aureus , has anti-inflammatory properties, and is a superoxide anion radical scavenger [ 19 ].…”
Section: Introductionmentioning
confidence: 99%